One Space Can Put Her in a Different Place - How Do We Inhabit Spaces Differently? - Youssef, Farida (AUC Knowledge Fountain, 2022)
In Egypt, a male-dominated society, women are forced to constantly negotiate with patriarchal systems. Dichotomies and paradoxes between principles governing different gendered roles, religion and cultural codes and westernization and commercialization have been continuously shaping Egyptian women’s status over the past decades. This is exhibited in public spaces, where women’s current preferences, perceptions and behavior emphasize the dominance of one gender over the other. This research aims for a better understanding of space inhabitance through a gendered lens. It questions the roles the society and the urban spaces play in the daily lives of women through examining women’s perception of public spaces - social and spatial factors shaping their perception (especially on their use of public space); the behavioral implications of their perception in space; and their needs and expectations from urban spaces. This study proceeds with the overarching question: how can the perception and experiences of middle-class Cairene women using public spaces inform the planning and design of such spaces? The underlying hypothesis being that social triggers and prejudices, and gender-class tensions shape women’s perceptions and hence affect their inclusiveness and behavior in public space. This research contributes to a better understanding of Cairene public spaces through a gendered lens, allowing for the future design of more inclusive public spaces, and revamping existing spaces as well, informed by our gendered dynamics.